Peirce' Semiology of Rinso Advertising's through Total Branding of Integrated Marketing Communication - Sampurna, Angelia; Putri, Ayu Faizah; Perkasa, Muhammad Iman Adi; Chinmi, Maichael; Marta, Rustono Farady (Palakka : Media and Islamic Communication, 2020)
The intense competition in the world of industry and business requires a company to be more creative to market its products. Companies will struggle to face their contenders without creativities, innovatives, and strategies to persuade prospectives consumers. One of the funnels to compete is to use advertising media. Advertising media as a means of communication used to deliver and disseminate messages which follow the marketing objectives, one of which is through total branding marketing. This study was to determine Charles Sanders Peirce's semiotic message based on the object, representant (sign), and interpretant with a qualitative approach through observation, content analysis, and data collection through library research. The results of the analysis of this research prove that advertising communication is no longer offering a clear and rigid product, but also through creative and attractive persuasive product of marketing. From a semiotic point of view, it can be seen that advertising does not only provide information about a product or service, it does not only try to market the product persuasively but has extended to specific situation conditioning in the target market. By using this Rinso Warna product, through advertisements, it can be seen that the stain on the clothes will disappear in the first wash, where the color of the clothes will be maintained even after several washing processes, hands will feel smooth.